1994
DOI: 10.1192/bjp.164.6.759
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Cognitive Therapy, Applied Relaxation and Imipramine in the Treatment of Panic Disorder

Abstract: Recent studies have shown that cognitive therapy is an effective treatment for panic disorder. However, little is known about how cognitive therapy compares with other psychological and pharmacological treatments. To investigate this question 64 panic disorder patients were initially assigned to cognitive therapy, applied relaxation, imipramine (mean 233 mg/day), or a 3-month wait followed by allocation to treatment. During treatment patients had up to 12 sessions in the first 3 months and up to three booster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
397
7
20

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 601 publications
(444 citation statements)
references
References 33 publications
20
397
7
20
Order By: Relevance
“…The effect sizes on the composite score were comparable to those found by Clark, et al (1994). While the difference in the effect size for the composite score at post-treatment between brief and standard therapy was significant, the effect size compared to wait-list for brief therapy was still large.…”
Section: Follow-upsupporting
confidence: 67%
See 1 more Smart Citation
“…The effect sizes on the composite score were comparable to those found by Clark, et al (1994). While the difference in the effect size for the composite score at post-treatment between brief and standard therapy was significant, the effect size compared to wait-list for brief therapy was still large.…”
Section: Follow-upsupporting
confidence: 67%
“…These were chosen to test the study hypotheses. The main analysis was based on a single unweighted composite panic-anxiety measure (Clark et al 1994;Connors, Epstein, March, Angold, Wells, Klaric et al, 2001). Additional analyses were conducted on individual panic/anxiety measures if significant between-group differences were found.…”
Section: Discussionmentioning
confidence: 99%
“…In direct comparisons of cognitive behaviour or exposure therapy with psychopharmacological treatment, drugs were superior in three studies (Bakker et al 1999;Black et al 1993;Mavissakalian and Michelson 1986). No differences were found in five studies (Clark et al 1994;Klosko et al 1990;Marks et al 1983;Sharp et al 1997;Telch et al 1985) and an open study (Dannon et al 2004), while one study showed inconsistent results .…”
Section: Monoamine Oxidase Inhibitors (Maoi)mentioning
confidence: 82%
“…In only one of six panic disorder studies, a longerlasting effect of CBT could be demonstrated . One study showed superiority of CBT, but the patients in the CBT group were allowed to use benzodiazepines, making the results difficult to interpret (Clark et al 1994). In one study, drug treatment was superior to CBT at follow-up (Loerch et al 1999).…”
Section: Monoamine Oxidase Inhibitors (Maoi)mentioning
confidence: 99%
“…Romano et al 35 observaram redução significativa da sensibilidade à ansiedade após seis semanas de tratamento com citalopram (ISRS), sugerindo que o medo das consequências de sensações corporais poderia ser normalizado pelo tratamento farmacológico e que um mecanismo serotonérgico poderia estar envolvido na modificação de uma distorção cognitiva presente no TP. Eles concluem que essa redução da sensibilidade à ansiedade após tratamento exclusivo com medicação contesta a ideia de que a diminuição da sensibilidade à ansiedade seja seletivamente mediada pelo tratamento cognitivo comportamental 36 .…”
Section: Discussionunclassified